Land development in the light of the objectives of Shariah (Maqasid) - Mohamad, Nor Asiah (2012)
The main objective of the Shariah is to provide a basis to govern all aspects of Muslim life socially, economically as well as politically. The ultimate goal of the Shariah is to be a blessing for mankind. This is the primary purpose for which the Prophet Muhammad (Saw) was sent to this world. There is also a common belief among all societies around the world that the primary purpose of development is to promote human well-being. In this respect, Islam also identifies some of the equally important and generally recognized requirements for sustained well-being as among others; the security of life, property and honor, individual freedom, moral as well as material education, marriage and family management and social solidarity, minimization of corruption, breach of trust, and fraud. It is argued that the spiritual foundation needed for the realization of the above lacks the emphasis that it needs. It is also argued that it may not be possible to promote sustainable development without ensuring adequate satisfaction of all these requirements. In this paper, the objectives of Shariah are addressed as the determining factors, which, if properly understood and translated into practice, would become a tool in realizing the mission towards sustainable development. This study highlights the importance of having a correct understanding of the objectives of the Shariah in land development and land management hence forms as framework in all policies or activities and helped prioritise in decision makings and actions. The method employed in this study is data collection based on primary and secondary sources and analysis of the opinion of the Muslim jurists on maqasid, land, land development and management.